Angle of repose of granulated ice: effect of wood ash - William M. Harris; Andrii Murdza; Erland M. Schulson (Journal of Glaciology)
New experiments have revealed that the addition of a small amount of wood ash doubles the angle of repose of granulated ice at −10°C, but has little effect at −30°C. It is hypothesized that this behavior may be explained in terms of the freezing of water that is formed at the higher temperature through the reaction of salt within the ash.